COBRA-HPA: a block generating tool to perform hybrid program analysis. (2019) - Huybrechts, Thomas; Bock, Yorick De; Li, Haoxuan; Hellinckx, Peter
The Worst-Case Execution Time (WCET) of a task is an important value in real-time systems. This metric is used by the scheduler in order to schedule all tasks before their deadlines. However, the code and hardware architecture have a significant impact on the execution time and thus the WCET. Therefore, different analysis methodologies exist to determine the WCET, each with their own advantages and/or disadvantages. In this paper, a hybrid approach is proposed which combines the strengths of two common analysis techniques. The two-layer hybrid model splits the code of tasks into so-called basic blocks. The WCET can be determined by performing execution time measurements on each block and statically combining those results. The COBRA-HPA framework presented in this paper is developed to facilitate the creation of hybrid block models and automate the measurements/analysis process. Additionally, an elaborated discussion on the implementation and performance of the framework is given. In conclusion, the results of the COBRA-HPA framework show a significant reduction in analysis effort while keeping sound WCET predictions for the hybrid method compared to the static and measurement-based approach.